The Jews in the twentieth century - Gilbert, Martin, 1936-2015. (New York : Schocken Books, 2001)
"What an extraordinarly chroncile of upheaval, sorrow, and achievement is the story of the Jews in the twentieth century - and who better to narrate it than the renowned British historian Sir Martin Gilbert, whose lifework has been the study of the events and personages of our time. In this illustrated volume he describes the individuals, the historic movements, the watershed moments, and the horrific years that so profoundly changed the world and the Jewish people." "In a text interwoven with and illuminated by more than 400 photographs, many of them never before published or long forgotten, we meet the widely dispersed turn-of-the-century Jewish communities of Europe, the Middle East, and Asia. Then we encounter with startling immediacy, the impassioned Zionists who set out to reclaim Palestine and the immigrant waves that poured out of Eastern Europe in search of a better life in America - among them, the brilliantly creative writers, composers, actors, and comedians who enthralled millions; and the scientists, judges, legislators, entrepreneurs, and intellectuals whose numbers can hardly be counted but whose thoughts and deeds shaped the modern world."--Jacket.
Maps of Europe and the Middle East -- Migration, Assimilation, the Promised Land -- The First World War -- The Crucible Years -- Challenge and Response -- The Second World War -- Rehabilitation, Statehood and Renewal -- Successes, Threats and Dilemmas -- Towards the Twenty-First Century.
Includes index.
Keywords: Jews -- History -- 20th century; Jews -- History -- 20th century -- Pictorial works; Jews; Joden; Juden; 1900 - 1952; History; Pictorial works